Joint Destruction Is Associated With All Types of Cardiovascular Events in French Rheumatoid Patients: A Real-Life Study With Very Long Follow-Up - Robert, Marie; Hot, Arnaud; Mifsud, François; Ndongo-Thiam, Ndiémé; Miossec, Pierre (Frontiers in Medicine, 2020)
Objective: Rheumatoid Arthritis (RA) leads to joint destruction but also to systemic manifestations with an increased incidence of cardiovascular events (CVE). Many studies have shown a link between RA severity and CV risk, but the duration of follow-up remains often insufficient to allow a conclusion. CVE definition was generally reduced to myocardial infarction and stroke, and few studies were conducted in non-Anglo-Saxon countries with low CV incidence. This study aimed to assess the relationship between joint destruction and the occurrence of different types of CVE in a large cohort of French RA patients with a long-term follow-up. Methods: This historical cohort study included 571 RA patients followed between 1992 and 2012 in Lyon, France. The primary endpoint was the first occurrence of a CVE. Logistic regressions were used to identify factors associated with CVE occurrence. Cox proportional hazard models were performed as separate analysis to take advantage of the long-term follow-up. Results: During a mean follow-up of 16.1 years, 30.3% of patients experienced a CVE, mostly acute arterial events. Joint destruction was associated with an increased risk of CVE (Odds-ratio=3.72 [95% CI, 1.09 to 15.35], p=0.047) among non-smokers RA patients. Survival analysis revealed that joint destruction was associated with a shorter time to onset of the first CVE only among non-smokers (Hazard-ratio=3.44 [CI, 1.07 to 11.04], p=0.038). Conclusion: Joint destruction is associated with CVE occurrence in RA patients from a population with lower incidence of CV disease. This study suggests that RA patients, and especially those with destruction, merit institution of precise guidelines to manage this CV risk and trials are required to evaluate them.